Effect of the secretome of mesenchymal stem cells overexpressing BMP‐9 on osteoblast differentiation and bone repair - Calixto, Robson Diego; Freitas, Gileade Pereira; Souza, Paola Gomes; Ramos, Jaqueline Isadora Reis; Santos, Isabela Cristine; de Oliveira, Fabiola Singaretti; Almeida, Adriana Luisa Gonçalves; Rosa, Adalberto Luiz; Beloti, Marcio Mateus (Journal of cellular physiology, 2023)
The secretome present in the conditioned medium (CM) of mesenchymal stem cells (MSCs) is a promising tool to be used in therapies to promote bone regeneration. Considering the high osteogenic potential of the bone morphogenetic protein 9 (BMP‐9), we hypothesized that the secretome of MSCs overexpressing BMP‐9 (MSCs BMP‐9 ) enhances the osteoblast differentiation of MSCs and the bone formation in calvarial defects. CM of either MSCs BMP‐9 (CM‐MSCs BMP‐9 ) or MSCs without BMP‐9 overexpression (CM‐MSCs VPR ) were obtained at different periods. As the CM‐MSCs BMP‐9 generated after 1 h presented the highest BMP‐9 concentration, CM‐MSCs BMP‐9 and CM‐MSCs VPR were collected at this time point and used to culture MSCs and to be injected into mouse calvarial defects. The CM‐MSCs BMP‐9 enhanced the osteoblast differentiation of MSC by upregulating RUNX2, alkaline phosphatase (ALP) and osteopontin protein expression, and ALP activity, compared with CM‐MSCs VPR . The CM‐MSCs BMP‐9 also enhanced the bone repair of mouse calvarial defects, increasing bone volume, bone volume/total volume, bone surface, and trabecular number compared with untreated defects and defects treated with CM‐MSCs VPR or even with MSCs BMP‐9 themselves. In conclusion, the potential of the MSC BMP‐9 ‐secretome to induce osteoblast differentiation and bone formation shed lights on novel cell‐free‐based therapies to promote bone regeneration of challenging defects.